Exploring AI applications in libraries: A topic modelling analysis of recent trends and themes - Masrek, Mohamad Noorman; Khan, Muhammad Kabir (Journal of Islamic, Social, Economics and Development, 2026)
This study examines the application of Artificial Intelligence (AI) in the field of library and information science using a topic modelling approach. By applying Latent Dirichlet Allocation on the titles, abstracts, and keywords of articles indexed in Scopus, we identify the primary themes within AI-related library research. Seven key topics emerged from the analysis, covering themes such as AI for student and academic engagement in libraries, AI integration in business and education, smart library services and information technology, knowledge and data management, machine learning for detection and recognition, data-driven models and classification techniques, and AI in language processing and information analysis. These findings highlight current priorities and emerging trends in AI applications within libraries, revealing both the scope of ongoing research and potential future directions for AI-enhanced library services. This study provides valuable insights for researchers, practitioners, and policymakers seeking to leverage AI to advance library functions and services.